Physiological Ca2+ Transients Versus Pathological Steady-State Ca2+ Elevation, Who Flips the ROS Coin in Skeletal Muscle Mitochondria - Li, Ang; Yi, Jianxun; Li, Xuejun; Zhou, Jingsong (Frontiers in Physiology, 2020)
Mitochondria are both the primary provider of ATP and the pivotal regulator of cell death, which are essential for physiological muscle activities. Ca2+ plays a multifaceted role in mitochondrial function. During muscle contraction, Ca2+ influx into mitochondria activates multiple enzymes related to tricarboxylic acid (TCA) cycle and oxidative phosphorylation, resulting in increased ATP synthesis to meet the energy demanding. Pathophysiological conditions such as skeletal muscle denervation or unloading also lead to elevated Ca2+ levels inside mitochondria. However, the outcomes of this steady-state elevation of mitochondrial Ca2+ level include exacerbated reactive oxygen species (ROS) generation, sensitized opening of mitochondrial permeability transition pore (mPTP), induction of programmed cell death and ultimately muscle atrophy. Previously, both acute and long-term endurance exercise has been reported to activate certain signaling pathways to counteract ROS production. Meanwhile electrical stimulation is known to help prevent apoptosis and alleviate muscle atrophy in denervated animal models and patients with motor impairment. There are various mechanistic studies focus on the excitation-transcription coupling framework to understand the beneficial role of exercise and electrical stimulation. Interestingly, a recent study has revealed an unexpected role of rapid mitochondrial Ca2+ transients in keeping mPTP at a close state with reduced mitochondrial ROS production. This discovery motivated us to contribute this review article to inspire further discussion about the potential mechanisms underlying differential outcomes of physiological mitochondrial Ca2+ transients and pathological mitochondrial Ca2+ elevation in skeletal muscle ROS production.